Physical Condition Profile of Volleyball Athletes Pomnas 2025 - Ahmad Luthfi Ramadhani; Arizky ramadhan; Iyakrus Iyakrus; Arif Hidayat; Reza Resah Pratama; M. Haris Satria; Adityo Agustiawan; Kevin Octara; Bojan Bjelica; Budiansyah Budiansyah (Sriwijaya University Learning and Education International Journal, 2026)
Physical condition is an important factor influencing volleyball performance, particularly in competitive events such as POMNAS 2025. An evaluation of athletes’ physical profiles is necessary to identify strengths and weaknesses that may affect performance during competition. Therefore, this study aimed to analyze the physical condition of volleyball athletes from Sriwijaya University participating in POMNAS 2025. This study employed a quantitative descriptive method involving 12 male volleyball athletes. The instruments used were based on the standards of the Ministry of Youth and Sports, including tests of flexibility (sit and reach), muscular strength (push-up, sit-up, and left-right hop tests), explosive power (vertical jump and medicine ball throw), speed (20 m sprint), agility (shuttle run), and endurance (beep test).The findings revealed that several physical components were still categorized as low, particularly flexibility, speed, and endurance. In contrast, upper-body strength showed relatively better results, while explosive power and agility were generally in the adequate category. These findings indicate that the athletes possess varying levels of physical readiness, with some components still requiring improvement to support optimal volleyball performance.In conclusion, the physical condition of the athletes has not yet reached an optimal level in several key components. Therefore, coaches are recommended to develop more structured and specific training programs focusing on flexibility, speed, and endurance enhancement to improve competitive performance.